An Assessment of sense of place in Kota Bharu cultural heritage zone among tourists - Nik Mohamad Aizat Nik Mohd Adib
There are many types of tourism and one of them is heritage tourism. In order to attract tourists to revisit and prolong their stay in historical sites, the sites must preserve its unique and authentic identity as well as its sense of place. Tourist who tends to revisit to same site or staying longer within the site is a proof of strong sense of place of that particular tourism site. Conflict arose in cultural identity and Islamic identity has caused tourist lack of excitement thus staying less longer in Kelantan tourism site and physical characteristic decrease in authenticity of Kota Bharu has caused tourist revisit number is low. This research assesses the relationship between sense of place and tourists’ frequency of visit and length of stay in Kota Bharu Cultural Heritage Zone based on Bott’s Psychometric Scale. This research’s methodology is based on the mixed method using both quantitative (questionnaire) and qualitative (interview). The sample consists of 445 respondents among domestic and international tourists. Statistical analysis of descriptive analysis and inferential analysis - ANOVA were the main methods used. 10 interviewees among government agencies officers and tourism businesses were involved in the structured interview as the medium for the validation of quantitative data of this study. In the research, sense of place of Kota Bharu Cultural Heritage Zone is significance in the context of length of stay which are ‘built environment scale’, ‘character scale’, ‘inherent socio-cultural scale’, ‘transactional socio-cultural scale’, ‘significant scale’, ‘aesthetic scale’, ‘informational scale’ and well-being scale’ while all scales of sense of place of Kota Bharu Cultural Heritage Zone are not significance in the context of frequency of visit since the area presents less influence on tourists’ decisions to revisit the heritage zone. The result indicates that the sense of place in Kota Bharu Cultural Heritage Zone has less influence on the tourists’ frequency of visit but does influence tourists’ length of stay in the zone. Hence, this study has identified and explored the gap in tourism research in terms of the relationship between sense of place and tourist behaviors, particularly tourists’ intentions to revisit and their duration of stay in a historical site. The findings are helpful to the government and business owners in planning attractions for tourist and sustaining the social and economic importance of historical areas.